Exploring the Potential of SGLT-2 Inhibitors in Cancer Treatment: Mechanisms, Preclinical Findings, and Clinical Implications - Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski; Sebastian Samuła; Michał Mazur; Dorota Waz; Jakub Szarłowicz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak (Quality in Sport)
Introduction Sodium-glucose co-transporter 2 (SGLT-2) inhibitors, originally developed for the treatment of type 2 diabetes, have recently attracted attention for their potential applications in oncology. Their potential to modulate tumor metabolism and enhance responses to cancer therapies is an area of increasing interest.